Effect of tumor-infiltrating lymphocytes depending on the presence of postmastectomy radiotherapy on the prognosis in pT1-2N1M0 breast cancer - Zhang, Lina; Tang, Tiantian; Liu, Lei; Li, Chunxiao; Li, Yuntao; Geng, Cuizhi (Frontiers in Oncology, 2023)
Background Currently, it remains unclear regarding the association between tumor-infiltrating lymphocytes (TILs) and the efficacy of postoperative radiotherapy in primary tumors. Here we attempted to investigate the effect of TILs depending on the presence of postmastectomy radiotherapy (PMRT) on the prognosis in pT1-2N1M0 breast cancer. Methods The clinical data of pT1-2N1M0 breast cancer patients undergoing mastectomy and axillary lymph node dissection were retrospectively analyzed. The effect of TILs on the prognosis was assessed based on the infiltration degree (low: TILs ≤10%, high: TILs >10%), and then the prognosis of patients with low and high infiltration of TILs was analyzed based on presence or absence of PMRT. Results Totally 213 patients were eligible for the study, including 162 cases of low infiltration and 51 of high infiltration. High-infiltration patients tended to be ER/PR-negative, HER2-positive, and have high histological grade. The infiltration in triple-negative and HER2-positive subtypes was higher compared with Luminal A subtype. Regarding local-regional recurrence-free survival, recurrence-free survival, and overall survival (OS) rates, the differences were all inapparent whether in high- and low-infiltration patients or in high-infiltration patients with/without PMRT. Compared with those without PMRT, low-infiltration patients with PMRT showed a significantly increased OS rate (92.8% vs. 80.0%, p=0.023). Multivariate analysis further confirmed PMRT as an independent predicator of OS in low-infiltration patients (HR: 0.228, 95%CI: 0.081-0.644, p=0.005). Conclusion High infiltration of TILs in pT1-2N1M0 breast cancer may be associated with clinicopathological factors. Low-infiltration patients, but not high-infiltration patients, may derive survival benefits from PMRT.